[PP.05.39] TWENTY-FOUR HOUR AMBULATORY BLOOD PRESSURE LEVEL IS CORRELATED WITH ALTERED PSYCHOLOGICAL PROFILES IN PATIENTS WITH APPARENTLY TREATMENT-RESISTANT HYPERTENSION. (September 2017) - Berra, E.; Petit, G.; George, C.; Capron, A.; Wallemacq, P.; de Timary, P.; Persu, A.
Abstract : Objective: Clinicians following patients with apparently treatment-resistant hypertension (aTRH) agree that a substantial proportion of these patients have a peculiar psychological profile. The latter may adversely affect blood pressure (BP) control, either by impacting drug adherence, or through other, poorly explored psycho-physiological mechanisms. The aims of this pilot study were to explore the psychological profile of patients with aTRH using validated questionnaires and to look for its relation with BP control and drug adherence. Design and method: Psychological profile was evaluated using the Emotion Regulation Questionnaire (ERQ), the Toronto Alexithymia Scale (TAS 20), the Cognitive Emotion Regulation Questionnaire (CERQ), the Brief Symptom Inventory (BSI) and the Post Traumatic Diagnostic Scale (PDS). Adherence status was assessed by urine drugs quantification using liquid chromatography-mass spectrometry assays. Results: The analysis included 35 consecutive outpatients with aTRH (mean age: 51 years, 54% females, office BP: 180/105 mmHg, 24-hour ambulatory BP: 160/100 mmHg, mean number of antihypertensive drugs: 4.9). Twenty-four hour systolic BP level adjusted for the number of antihypertensive drugs significantly (p < 0.05) correlated with alexithymia (TAS 20; r = 0.50), in particular difficulty to identify and describe feelings (r = 0.47 and 0.45); with self-blame (r = 0.65), rumination (r = 0.59), dramatization (r = 0.63), blame of others (r = 0.46) and more generally non-adaptive strategies in the cognitive regulation of emotions (r = 0.72) assessed by CERQ; with anxiety (r = 0.51), depression (r = 0.46) obsession (r = 0.47), hostility (r = 0.51) and paranoia (r = 0.63) evaluated with BSI; with intrusion (r = 0.66) and avoidance/blunted emotional perception (r = 0.69) assessed by PDS. Despite a high proportion of partly adherent (40%) or non-adherent (31%) patients, these correlations remained unaffected after adjustment for adherence. Adherence level was not associated with BP level, the number of antihypertensive drugs or the aforementioned psychological characteristics. Conclusions: While poor drug adherence is common in patients with aTRH, it does not entirely explain poor BP control. Our results suggest that, in patients with aTRH, resistance to drug treatment is influenced by a deleterious constellation of psychological characteristics, irrespective of drug adherence. More research is needed to confirm these results, explore the underlying mechanisms and define the best strategies to improve BP control in this challenging subset of patients.